2017
DOI: 10.1177/0033354917709542
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Public Health Surveillance and Information Dissemination at the Centers for Disease Control and Prevention

Abstract: Public health surveillance is the foundation of effective public health practice. Public health surveillance is defined as the ongoing systematic collection, analysis, and interpretation of data, closely integrated with the dissemination of these data to the public health practitioners, clinicians, and policy makers responsible for preventing and controlling disease and injury.1 Ideally, surveillance systems should support timely, efficient, flexible, scalable, and interoperable data acquisition, analysis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 20 publications
0
48
2
5
Order By: Relevance
“…Input from hospital-, county-, and citylevel project staff was critical for the development of the project dashboard and also helped strengthen relationships across the various jurisdictions. 11,[13][14][15] Project staff could monitor the AFI surveillance project as soon as case data and laboratory results were entered into the web-based database. Because raw TAC results were forwarded to the University of Virginia for review and verification, and to avoid additional data entry work by project staff at Guangdong CDC or YIPD, China CDC uploaded the TAC results directly into the AFI database.…”
Section: Real-time Visualization Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Input from hospital-, county-, and citylevel project staff was critical for the development of the project dashboard and also helped strengthen relationships across the various jurisdictions. 11,[13][14][15] Project staff could monitor the AFI surveillance project as soon as case data and laboratory results were entered into the web-based database. Because raw TAC results were forwarded to the University of Virginia for review and verification, and to avoid additional data entry work by project staff at Guangdong CDC or YIPD, China CDC uploaded the TAC results directly into the AFI database.…”
Section: Real-time Visualization Of Datamentioning
confidence: 99%
“…11,14 This decision also helped to strengthen trust between project partners, which is essential for all effective public health surveillance projects. 12,15 According to project staff, the EDDC-AFI surveillance system was easy to use, flexible (could be modified to address changes in reporting requirements, eg, adding fields for JE and YF vaccination), included a feedback mechanism, safeguarded patient confidentiality, and ensured local data ownership. These characteristics likely strengthened local ''buy-in'' and probably improved data quality and should be considered when designing and deploying new surveillance systems.…”
Section: Data Ownership and Local Engagementmentioning
confidence: 99%
“…Proses yang saling berhubungan inilah yang menjadikan dasar alasan pengembangan basis data surveilans OMKABA harus dilakukan. Hasil interpretasi surveilans terintegrasi dengan penyebaran data terhadap praktisi kesehatan masyarakat, dokter, dan pembuat kebijakan yang bertanggung jawab untuk mencegah dan mengendalikan penyakit atau cidera (Richards et al, 2017).…”
Section: Pembahasanunclassified
“…Public Health Surveillance (PHS) is defined as the ongoing systematic gathering, analysis, and interpretation of data, closely integrated with the dissemination of these data to the public health practitioners, clinicians, and policy makers responsible for preventing and controlling disease and injury [1]. In the last decade, many experiments have demonstrated that social media data can help public health officials to detect potential outbreaks, forecast disease trends, monitor emergency situations and gauge disease awareness and reactions to official health communications [2,3].…”
Section: Introductionmentioning
confidence: 99%